Examining the relationship between road traffic accidents and the environmental factors using spatial statistics - Mbano, Arshley (Midlands State University, 2018)
This research presents an approach to examine the relationship between road traffic accidents and the environmental factors using spatial statistics. Road accident data for this research study was acquired from Leeds City Council database for the years 2009 to 2016.Other used datasets were obtained from OSM and DivaGis websites. To examine spatial patterns of road traffic accidents in the city of Leeds, network kernel density estimation was used to determine the road accident hotspots for reported accidents. The results revealed that some road segments have higher accident rates compared to some road segments that never had even a single reported road accident since 2009 to 2016. Ordinary Least squares technique was conducted to test the relationships between the dependent variable (road traffic accidents) and independent variables (retail outlets, recreational areas, public areas, liquor outlets and street furniture). Moran’s I statistics was used to assess for spatial autocorrelation in the datasets. The result of this research show that the proximity of retail outlets, recreational areas, public places, liquor outlets and street has a strong correlation with the number of road traffic injury incidents.